The systemic view as a basis for philological thought - Valentinova, Olʹga Ivanovna; Denisenko, Vladimir Nikiforovič; Preobraženskij, Sergej Jurʹevič; Rybakov, Michail Anatolʹevič (Lexington Books, 2021)
"In A Systemic View as the Base of Philological Thought, Olga Valentinova, Vladimir Denisenko, Sergey Preobrazhenskii, and Mikhail Rybakov explore the interrelation of language material, structure, and functions in various subjects of philological research, such as grammatical systems of language, semantics, linguistic personality, literary text, and formal aspects of verse. Their systemic approach is rooted in the theories of Wilhelm von Humboldt and his followers, including Russian scholars Alexander Potebnya, Gustav Shpet, and more recently Gennadii Prokop'evichMel'nikov (1928-2000). The authors use the concept of systemicity as an opportunity to see the studied whole in development, to show the functional interaction of linear and supra-linear connections, to explain their interdependence, and to predict further changes within the system. This book displays the scientific potential of the systemic approach to linguistics and related spheres, employing the framework of systematicity to revise the modern trends of philology and to map out an alternative paradigm for linguistic and philological thought that could restore the status of philology as a holistic science"--
Includes bibliographical references and index